Cover Picture: Omniligase‐1: A Powerful Tool for Peptide Head‐to‐Tail Cyclization (Adv. Synth. Catal. 12/2017). Issue 12 (18th May 2017) - Schmidt, Marcel; Toplak, Ana; Quaedflieg, Peter J. L. M.; Ippel, Hans; Richelle, Gaston J. J.; Hackeng, Tilman M.; van Maarseveen, Jan H.; Nuijens, Timo
Abstract : The inside cover picture, provided by Nuijens and co‐workers, illustrates the power and versatility of the peptide ligase omniligase‐1. This ligase provides a promising green and clean alternative to chemical approaches used for peptide cyclization, peptide fragment condensation and protein labelling. The ligations are traceless, proceed with very high catalytic efficiency and result in high product yields. Details on omniligase‐mediated peptide cyclization can be found in the communication on pages 2050–2055 (M. Schmidt, A. Toplak, P. J. L. M. Quaedflieg, H. Ippel, G. J. J. Richelle, T. M. Hackeng, J. H. van Maarseveen, T. Nuijens, Adv. Synth. Catal .2017, 359, 2050–2055; DOI:10.1002/adsc.201700314 ).